Sidt2 is a key protein in the autophagy-lysosomal degradation pathway and is essential for the maintenance of kidney structure and filtration function - Meng-ya Geng; Lizhuo Wang; Ying-ying Song; Jing Gu; Xin Hu; Cheng Yuan; Meng Yang; Wen-jun Pei; Yao Zhang; Jia-lin Gao (Cell Death and Disease, 2021)
Abstract The regulation and homeostasis of autophagy are essential for maintaining organ morphology and function. As a lysosomal membrane protein, the effect of Sidt2 on kidney structure and renal autophagy is still unknown. In this study, we found that the kidneys of Sidt2 −/− mice showed changes in basement membrane thickening, foot process fusion, and mitochondrial swelling, suggesting that the structure of the kidney was damaged. Increased urine protein at 24 h indicated that the kidney function was also damaged. At the same time, the absence of Sidt2 caused a decrease in the number of acidic lysosomes, a decrease in acid hydrolase activity and expression in the lysosome, and an increase of pH in the lysosome, suggesting that lysosomal function was impaired after Sidt2 deletion. The accumulation of autophagolysosomes, increased LC3-II and P62 protein levels, and decreased P62 mRNA levels indicated that the absence of the Sidt2 gene caused abnormal autophagy pathway flow. Chloroquine experiment, immunofluorescence autophagosome, and lysosome fusion assay, and Ad-mcherry-GFP-LC3B further indicated that, after Sidt2 deletion, the production of autophagosomes did not increase, but the fusion of autophagosomes and lysosomes and the degradation of autophagolysosomes were impaired. When incubating Sidt2 −/− cells with the autophagy activator rapamycin, we found that it could activate autophagy, which manifested as an increase in autophagosomes, but it could not improve autophagolysosome degradation. Meanwhile, it further illustrated that the Sidt2 gene plays an important role in the smooth progress of autophagolysosome processes. In summary, the absence of the Sidt2 gene caused impaired lysosome function and a decreased number of acidic lysosomes, leading to formation and degradation disorders of the autophagolysosomes, which eventually manifested as abnormal kidney structure and function. Sidt2 is essential in maintaining the normal function of the lysosomes and the physiological stability of the kidneys.